SWS Brain-Wave Music May Improve the Quality of Sleep: An EEG Study - Gao, Dongrui; Long, Siyu; Yang, Hua; Cheng, Yibo; Guo, Sijia; Yu, Yue; Liu, Tiejun; Dong, Li; Lu, Jing; Yao, Dezhong (Frontiers in Neuroscience, 2020)
Aim. This study investigated the neural mechanisms of brain-wave music on sleep quality. Background. Sleep disorders are a common health problem in our society and may result in fatigue, depression and problems in daytime functioning. Previous studies have shown that brain-wave music generated from electroencephalography (EEG) signals could emotionally affect our nervous system and have positive effects on sleep. However, the neural mechanisms of brain-wave music on the quality of sleep need to be clarified. Methods. Thirty-three young participants were recruited and randomly divided into three groups. The participants listened to rapid eye movement (REM) brain-wave music (Group 1: 13 subjects), slow-wave sleep (SWS) brain-wave music (Group 2: 11 subjects) or white noise (control group: 9 subjects) for 20 minutes before bedtime for six days. EEG and other physiological signals were recorded by polysomnography. Results. We found that the sleep efficiency increased in SWS group, but decreased in REM and WN group. The sleep efficiency in SWS group was ameliorated (t(10) = -1.943, p = 0.076). In the EEG power spectral density analysis, the delta power spectral density in REM group and in the control group increased, while that in SWS group decreased (F(2,31) = 7.909, p = 0.005). In the network analysis, the functional connectivity (FC), assessed with Pearson correlation coefficients, showed that the connectivity strength decreased (t(10) = 1.969, p = 0.073) between the left frontal lobe (F3) and left parietal lobe (C3) in SWS group. In addition, there was a negative correlation between the FC of the left frontal lobe and the left parietal lobe and sleep latency in SWS group (r = -0.527, p = 0.064). Conclusion. SWS brain-wave music may have a positive effect on sleep quality while REM brain-wave music or white noise may not have a positive effect. Furthermore, better sleep quality might be caused by a decrease in the power spectral density of the delta band of EEG and an increase in the FC between the left frontal lobe and the left parietal lobe. SWS brain-wave music could be a safe and inexpensive method for clinical use if confirmed by more data.